509 Role of blood gas bilirubin measurements and treatment for Neonatal Jaundice in neonates. (17th August 2022) - Alam, Naveed; Sidahmed, Mona; Kapoor, Sonal; Nadeem, Muhammad; Joshi, Mehul Kumar
Abstract : Aims: Hyperbilirubinemia is common in the first week of life with 60%–80% of babies developing jaundice. Though usually uncomplicated, untreated hyperbilirubinemia can lead to irreversible neurological injury. Prevention of bilirubin-induced neurological dysfunction includes universal risk factor and clinical assessment with Total serum bilirubin assessment. Point of care testing has the advantage of rapid bedside results, improving outcomes. Bilirubin measurement is available via blood gas analysers in most children hospital emergency departments and on the wards. Studies have shown good accuracy and precision of blood gas bilirubin compared with standard serum bilirubin assessment. Children's Hospital at Leicester has been using Gas Bili as well as Serum Bilirubin for the detection and treatment of babies having exaggerated physiological Jaundice in term and preterm neonates in the past, however since Mid-November 2021 using gas bilirubin alone has been as a standard practice to aim for improved patient care, rapid turn over and quick decision making. Methods: retrospective analysis of the investigations and care provided to neonates comparing the serum (Laboratory bilirubin) vs gas analysis for the months of October 2021 till end of Jan 2022. Analysing patient data on ICE, CITO and medical notes, we will be able to collect and analyse the data to see if any improvements have been noted in the quality of care. Results: results will be available once data collection process has been completed and will be shared. Conclusion: Data collection in progress- however It has been agreed by the children's Hospital children hospital emergency departments and admission teams (General Paediatrics team for the wards) to replace the use of Lab Bilirubin measurements with the Blood gas Bilirubin measurement for this will prove to be more cost effective, timely and robust measures for quick decision making and initiation of treatment and monitoring of the treatment response